Classification approaches in unmanned aerial vehicle (UAV) intrusion detection data set by using big data analysis. (2022) - Sivachandran, M.; Krishnakumar, T.
Abstract: The Multilayer Perceptron produces the high level of accuracy i.e., 72.7% accuracy level. The Logistic approach produces the 81.45% of precision value. This is the highest precision value compare with other model. Rest of the algorithms namely Gaussian Processes, Linear Regression, Multilayer Perceptron and SGD have produce the precision values from 71 to 81%. The Multilayer Perceptron approach takes low time consumption like 0.09 s to build the model, the Next SGD approach takes 0.12 s to build the model, the Next Logistic approach takes the 0.18 s, the Next Gaussian Processes approach takes the 0.2 s and finally Linear Regression approach takes more time around 0.21 s to build the model. The Linear Regression, Multilayer Perceptron have produces the recall value most nearly with Gaussian Processes. Rest of the approaches like SGD results vast difference with our optimal results and Logistic has very low and vast difference with our optimal approaches. AI strategies are used in an ever-increasing number of true applications including limitations on computational spending plans, the precise incorporation of such imperatives into the cycle of model choice, and model improvement is needed to an expanding degree.